3032 – MOUSE MULTIPOTENT PROGENITOR 5 CELLS ARE LOCATED AT THE INTERPHASE BETWEEN HEMATOPOIETIC STEM AND PROGENITOR CELLS - Sommerkamp, Pia; Romero-Mulero, Mari Carmen; Narr, Andreas; Ladel, Luisa; Hustin, Lucie; Schönberger, Katharina; Renders, Simon; Altamura, Sandro; Zeisberger, Petra; Jäcklein, Karin; Klimmeck, Daniel; Rodriguez-Fraticelli, Alejo; et al. (Experimental hematology, 2021)
Hematopoietic stem cells (HSCs) and distinct multipotent progenitor (MPP) populations (MPP1-4) contained within the Lin- Sca-1+ c-Kit+ (LSK) compartment have previously been identified using diverse surface-marker panels. Here, we phenotypically define and functionally characterize MPP5 (LSK CD34+ CD135- CD48- CD150-) and MPP6 (LSK CD34- CD135- CD48- CD150-) (Sommerkamp et al., Blood 2021). Upon transplantation, MPP5 supports initial emergency myelopoiesis followed by stable contribution to the lymphoid lineage, while MPP6 exhibits a more stem cell-like behavior. MPP5, capable of generating MPP1-4 but not HSCs, represents a dynamic and versatile component of the MPP network. To characterize all hematopoietic stem and progenitor cells, we performed RNA-sequencing (RNA-seq) analysis to identify specific transcriptomic landscapes of HSCs and MPP1-5. This was complemented by single-cell RNA-seq analysis of LSK cells to establish differentiation trajectories from HSCs to MPP1-5. In agreement with functional reconstitution activity, MPP5 is located immediately downstream of HSCs but upstream of the more committed MPP2-4. This study provides a comprehensive analysis of the LSK compartment, focusing on the functional and molecular characteristics of the newly defined MPP5 subset.